KUANTITAS PEMESANAN EKONOMIS BAHAN BAKU TEPUNG PADA USAHA ROTI SURYA BAKERY KOTA BANGKULU - Virda Palupi; Trisna Murni; Syamsul Bachri; Sri Warsono (Unib Press Universitas Bengkulu, 2017)
This study aimed to analyze the Economic order quantity level of raw material wheat flour for Surya Bakery and the quantity level of Re-order Point. The design of study was descriptive qualitative. The study used secondary data in order to gain the information about purchasing of raw material of flour. The data analyzed by quantitative method which used Economic Order Quantity (EOQ) method and Re-order Point. The result shows that EOQ in Usaha Roti Surya Bakery is 4.266 kg with frequency of ordering raw material is 22 times. Wher eas re-order point of the raw material when inventory reach 1.068 kg with lead time are 4 days. Before using EOQ method, the frequency of ordering raw material of flour is 36 times per year. After using EOQ method, it is found the frequency of ordering raw material of flour is 22 times per year. So that, after using EOQ method, the result of ordering cost was Rp. 2.668.00,- carrying cost was Rp. 2.615.000,-, and total cost of raw material was Rp. 5.283.000,-. Therefore, the Surya-Bakery could save money for Rp 533.000 per year.